(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the situation of using prophylactic antibiotics in endovascular interventions at the 30/4 hospital – Ministry of Public Security. Subjects and methods: Prospective, cross-sectional and comparative study on 95 patients who received antibiotic prophylaxis when performing endovascular intervention’s diagnosis and treatment techniques at the Department of Interventional Cardiology, the 30/4 hospital - Ministry of Public Security from June 2020 to June 2021. Results: The majority of patients in the study received parenteral antibiotic prophylaxis, accounting for 60.00%. The group of cephalosporin antibiotics was used the most with 84.21%. In which, the antibiotic cefazolin was used the most, accounting for 42.11%, followed by the antibiotic cefuroxime with 34.74%. The rate of systemic and local infections was higher in the oral antibiotic group than in the parenteral antibiotic group. Conclusion: The most commonly used cephalosporin group of antibiotics. The rate of systemic and local infections was higher in the oral antibiotic group than in the parenteral antibiotic group.